Correlation between sleep and multimorbidity in community-dwelling older adults in Hunan Province: a cross-sectional study - Su, Manman; Zhou, Yang; Chen, Wenhui; Liu, Yanping (Frontiers in Public Health, 2025)
BackgroundThe aim of this study was to provide global estimates of the prevalence of sleep quality and chronic diseases and to analyze the correlation between sleep and multimorbidity in community-dwelling older adults (≥65 years) in China.MethodsThis is a cross-sectional study and a stratified multistage random sampling method was used to collect data on demographic characteristics, the Pittsburgh Sleep Quality Index (PSQI), and assessment of chronic conditions. Chi-squared tests, t-tests, Wilcoxon rank sum test and analysis of variance were used to test the correlation between sleep and multimorbidity.ResultsOf the 1,173 community-dwelling older adults enrolled, the mean total PSQI score was 7.25 ± 4.23. Of these, 588 (50.1%) had a total PSQI score >7 (with poor sleep quality) and 920 (78.4%) had chronic diseases. In addition, 43.8% (403/920) had a single chronic disease and 56.2% (517/920) had multimorbidity. A combination of two and three chronic conditions dominated the pattern of multimorbidity among community-dwelling older adults. Overall, the prevalence of poor sleep quality with multimorbidity among community-dwelling older adults in the community was 57.6% (298/517). The prevalence of poor sleep quality in older adults with multimorbidity was 1.30 times higher than in those without multimorbidity (RR = 57.6%/44.2% = 1.30). The prevalence of poor sleep quality increased with the number of chronic conditions, and women had a higher prevalence of poor sleep quality than men. T-test and analysis of variance showed statistically significant differences in all seven components of the PSQI between those with and without multimorbidity and different numbers of chronic conditions (p < 0.05).ConclusionCommunity-dwelling older adults with multimorbidity were more likely to have sleep problems. The number of chronic conditions also had an additive effect on sleep problems, and women reported poorer sleep quality than men. One of the most challenging aspects of falling asleep was for participants with multimorbidity.